2005
DOI: 10.1128/aem.71.9.5138-5144.2005
|View full text |Cite
|
Sign up to set email alerts
|

New Chitosan-Degrading Strains That Produce Chitosanases Similar to ChoA of Mitsuaria chitosanitabida

Abstract: The betaproteobacterium Mitsuaria chitosanitabida (formerly Matsuebacter chitosanotabidus) 3001 produces a chitosanase (ChoA) that is classified in glycosyl hydrolase family 80. While many chitosanase genes have been isolated from various bacteria to date, they show limited homology to the M. chitosanitabida 3001 chitosanase gene (choA). To investigate the phylogenetic distribution of chitosanases analogous to ChoA in nature, we identified 67 chitosan-degrading strains by screening and investigated their physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…PF00933). Thus, our results showed that the primers designed for a GH80 family chitosanase by Yun et al (43) with little degeneracy can be used to amplify a GH3-like chitosanase-encoding gene of Anabaena (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…PF00933). Thus, our results showed that the primers designed for a GH80 family chitosanase by Yun et al (43) with little degeneracy can be used to amplify a GH3-like chitosanase-encoding gene of Anabaena (Fig. 1).…”
Section: Discussionmentioning
confidence: 92%
“…CsO-2. Yun et al (43) described a set of specific primers to detect new strains for production of chitosanases similar to chitosanase A of Mitsuaria chitosanitabida. In the current study, we used the same set of primers to amplify a chitosanase-encoding gene from two Anabaena species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH-5 and GH-8 contain a variety of glycoside hydrolases, such as chitosanase, cellulase, licheninase, and endo-1,4-␤-xylanase, whereas, GH-46, GH-75, and GH-80 are currently exclusively classified for chitosanase. Among these families, GH-46, especially those from Bacillus (17) and Streptomyces strains (18), have been studied extensively for their catalytic features (18), enzymatic mechanisms (19), and protein structures (20), whereas GH-75 and GH-80 have only been studied for protein purification (11)(12)(13)(14) and gene cloning (21,22). An interesting finding is that all GH-75 chitosanases are fungal enzymes, such as those from Aspergillus (11,14), Penicillium (12), Beauveria (GenBank TM accession number AY008269), Cordyceps (GenBank TM accession number AY008269), Fusarium (13), Hypocrea (GenBank TM accession number AY571342), Magnaporthe (GenBank TM accession number AACU01000927), Metarhizium (GenBank TM accession number AJ293219), and Neurospora (GenBank TM accession number AABX01000003).…”
mentioning
confidence: 99%
“…Based on similarity of amino acid sequences, GH has been classified into 115 families [http://www.cazy.org/], among which GH-5 [Tanabe et al, 2003], -8 [Mitsutomi et al, 1998;Kimoto et al, 2002;Yatsunami et al, 2002;Choi et al, 2004;Kim et al, 2004;Ogura et al, 2006], -46 [Masson et al, 1994[Masson et al, , 1995Akiyama et al, 1999;Shimosaka et al, 2000;Yoon et al, 2000;Lee et al, 2006], -75 [Zhang et al, 2001;Shimosaka et al, 2005;Cheng et al, 2006] and -80 [Park et al, 1999;Yun et al, 2005] are known to have chitosanase activity. Founded on substrate specificity, these chitosanases have been further divided into 3 subclasses [Izume et al, 1992;Fukamizo et al, 1994Fukamizo et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%